Robust nonlinear isolators based on frozen mode exceptional point degeneracies - Serena Landers; William Tuxbury; Ilya Vitebskiy; Tsampikos Kottos (Physical Review Research)
We introduce a class of imperfection-protected nonlinear isolators designed to operate at exceptional point degeneracies (EPDs) of the Bloch modes of periodic photonic structures. These Bloch EPDs are responsible for slow light and the emergence of a scattering frozen mode regime (FMR). When a weak spectral asymmetry is introduced, the group velocity in their proximity varies sharply, boosting the directional nature of the nonlinear interactions and leading to extreme isolation.